A educação física no Instituto Madre Marta Cerutti de Barra do Garças, MT : 1971 - 1985 - Assis, Rodrigo Amancio de (2020)
The confessional schools are present in a great part of the Brazilian territory, graduating people in different levels of education, disseminating its teaching, practices and values. In the state of Mato Grosso, among the best-known religious confessional schools there is the Salesian, which spread from the capital to the countryside cities, such as Barra do Garças, where this research took place. Therefore, the following question emerged: how did the process of schooling of Physical Education discipline occurred in the Madre Marta Cerutti Institute in the city of Barra do Garças between the years of 1971 and 1985? In this regard, the general aim of this research is to investigate the schooling process of the Physical Education discipline in the Madre Marta Cerutti Institute in the city of Barra do Garças/MT between the years 1971 and 1985. Specifically, it searches: to identify the existence of legal alterations (Laws 5.692/71, 6.251/75 and the Decree 69450/71) in which it refers to the Physical Education in the Madre Marta Cerutti Institute; to verify the existence of the curricular proposal of Physical Education in the Madre Marta Cerutti Institute; to identify the corporal practices used by the teachers in the Physical Education classes; to identify the treatment given to the bodies and clothing of the students in the several spaces of the school and during the exercises of corporal practices. This research has as theoretical-methodological support the cultural history, the qualitative approach, which the primary sources of consultation were the files of the Madre Marta Cerutti Institute (meeting proceedings, news report, photographs, videos, books, periodic, among other forms of record). It was also used the oral history methodology, allowing managers and former managers, teachers, former teachers and students to be heard in the aforementioned period. Two teachers, 20 egresses and one former employee were heard. The results show that the Madre Marta Cerutti Institute, private, confessional school, maintained and administered by the Filhas de Maria Auxiliadora Institute, throughout the study offered pre-school to high school education. In all of the curricular structures consulted it was identified the offer of the Physical Education classes, however, the analysis showed that the representations about the subject pointed to the dominant presence of corporal sportive practices which aimed the development of the technique and the physical aptitude, that was very common in the time. It appears in the imagination of the egresses that some modalities were more destined to men and other to women. It was identified that, specifically, the Law 6.251/75 did not produce perceptible changes to the eyes of the investigated teachers. We highlight that this thesis was developed in the Research line School Cultures and Languages and it is inserted in the Study and Research Group in School Physical Education and Pedagogical Practices (hereby GEEFE).